A gestão orçamentária da UFS no período de 1998 a 2008 - Vasconcelos, Geovânia Moura (2010)
This study aims to examine the budget management of the Federal University of Sergipe (UFS) in the period 1998 to 2008. Specifically, it seeks: a) analyze the composition of the resources of UFS highlighting the obstacles and alternatives to enlarge capture of revenue, b) present the costs to the institution, explaining the effect measures for its control, c) explain the accomplishments achieved through the actions budget executed, d) list the main results obtained and investments through direct appropriation, the parliamentary amendments, the highlights and the actions developed in extrabudgetary UFS. For development of research, we used the following resources: documents taken from the Financial Management System (SIAFI), Federal Government's Management Reports for t of this work and literature inherent to the subject. Among the results, we highlight the following: i) as to finance - the raising of funds through decentralization of credit from projects and partnerships is an important alternative to top up the credit institution's budget; ii) as to the allocation of expenditure - the establishment excels for cost containment with the applicability of measures for the rational use of resources, iii) as to the performance of the institution - there is an exponential increase in activities related to teaching, research and extension expressed by the increased number of courses and vacancies for undergraduate and graduate, as highlighted by the indexed publications. Partnerships have provided funding to exogenous UFS appropriate infrastructure for development of scientific and technological research in the state of Sergipe, besides promoting the articulation of the institution different external sectors, iv) on the Budget Process - the institution has conducted much of budget. The difficulties faced by UFS are inherent in every university in the national scene, like the excessive bureaucracy, the primacy of the accounting procedures and financial control bodies, to the detriment of the physical implementation of IFES. Suggestions are proposed to improve the management of the allocation of human, material and financial resources.